DOI: 10.11606/t.11.2014.tde-04122014-081956
|View full text |Cite
|
Sign up to set email alerts
|

Nutrição e fertilização de plantações clonais de eucalipto sob diferentes condições edafoclimáticas

Abstract: À minha mãe, Roseli, pelo carinho, dedicação e amor com os quais nunca cessou de nos ensinar. Ao meu irmão Marcel, por me acompanhar por tantos anos, sempre demonstrando seu afeto. À minha futura esposa, Thais, por me acompanhar e compartilhar meus momentos de alegria e aflições, sempre me incentivando e apoiando. Já não consigo me definir sem pensar em você, somos um. Aos meus familiares, Djailson, Vó Maria, Tia Áurea, Tia Rosane, Tio Alexandre, Luís Fernando, Patrícia e José Roberto pela união e dedicação mú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Efetuou-se o plantio e a partir deste momento, a cada 2, 6, 10 e 14 dias, pesavam-se alguns vasos de cada turno de rega, determinando o peso médio destes, com o solo na umidade atual e se procedia a irrigação, visando a voltar o vaso ao peso com o solo úmido. Esse procedimento foi determinado, seguindo as recomendações de Melo et al (1998). Paralelamente, foram conduzidos quatro vasos de cada turno de rega para controle do aumento de peso das mudas, foram feitas correções dos pesos médios dos vasos, aos 45 e 90 dias, após o plantio.…”
Section: Methodsunclassified
“…Efetuou-se o plantio e a partir deste momento, a cada 2, 6, 10 e 14 dias, pesavam-se alguns vasos de cada turno de rega, determinando o peso médio destes, com o solo na umidade atual e se procedia a irrigação, visando a voltar o vaso ao peso com o solo úmido. Esse procedimento foi determinado, seguindo as recomendações de Melo et al (1998). Paralelamente, foram conduzidos quatro vasos de cada turno de rega para controle do aumento de peso das mudas, foram feitas correções dos pesos médios dos vasos, aos 45 e 90 dias, após o plantio.…”
Section: Methodsunclassified
“…On the day plants were sown, the soil in the T m control pots received mineral fertilization consisting of 300 mg N (ammonium sulfate), 150 mg P (triple superphosphate), and 100 mg K (potassium chloride) per kg soil. The pots also received 30 mL of a micronutrient solution (0.96 g boric acid, 1.97 g copper sulfate pentahydrate, 3.08 g manganese sulfate tetrahydrate, 0.09 g sodium molybdate dihydrate, and 7.33 g zinc sulfate per liter) and 10 mL of a Fe-EDTA solution (Melo et al, 1998). In the WTS treatments, NPK was added to complete the content of these nutrients applied to the T m treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Such an increase can be explained by biogeochemical cycling process, mainly because K was the third-most transferred nutrient to the soil via senescent leaf deposition (Figure 4f). Melo (2014) found that K increased between 24 and 48 months in one forest site and attributed this to the nutrient cycling process arising from the deposition of branches and leaves. According to Gonçalves et al (2008), this process starts in the second year of the Eucalyptus crop cycle, when the closure of the forest canopy occurs, and is responsible for the mineralization of the nutrients contained in the litter.…”
Section: Silva (2011) Evaluated the Effects Of Fertilization Levels Amentioning
confidence: 96%
“…Quarztzarênico (Entisol) show that K splitting reduces its leaching in the soil, with the fast K absorption by the crop being the main factor responsible for its decrease in the soil (Silva et al, 2013;Melo, 2014).…”
Section: Silva (2011) Evaluated the Effects Of Fertilization Levels Amentioning
confidence: 99%
See 1 more Smart Citation